Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (2x+1)^2+2(4x^2-2)+(2x-1)^2=4x2+4x+1+8x2-4+4x2-4x+1=16x2-2
`Answer:`
`a)`
`A=5(x+1)^2-3(x-3)^2-4(x^2-4)`
`=>A=5(x^2+2x+1)-3(x^2-6x+9)-4x^2+16`
`=>A=5x^2+10x+5-3x^2+18x-27-4x^2+16`
`=>A=(5x^2-3x^2-4x^2)+(10x+18x)+(5-27+16)`
`=>A=-2x^2+28x-6`
`b)`
`B=5(x+1)^2-3(x-3)^2-4(x+2)(x-2)`
`=2x(3x+5)-3(3x+5)-2x(x^2-4x+4)-[(2x)^2-3^2]`
`=6x^2+10x-9x-15-2x^3+8x^2-8x-4x^2+9`
`=(6x^2-4x^2+8x^2)-2x^3+(10x-9x-8x)+(-15+9)`
Thay `x=-7` vào ta được:
`B=10(-7)^2-2(-7)^3-7(-7)-6`
`=>B=10.49-2(-343)+49-6`
`=>B=490+686+49-6`
`=>B=1219`
\(A=\left(\frac{5x+2}{x^2-10x}+\frac{5x-2}{x^2+10x}\right).\frac{x^2-100}{x^2+4}\)
\(=\left(\frac{\left(5x+2\right)\left(x+10\right)+\left(5x-2\right)\left(x-10\right)}{x\left(x^2-100\right)}\right).\frac{x^2-100}{x^2+4}\)
\(=\frac{10\left(x^2+4\right)}{x\left(x^2-100\right)}.\frac{x^2-100}{x^2+4}=\frac{10}{x}\)
Với \(x=20040\)
\(\Rightarrow A=\frac{10}{20040}=\frac{1}{2004}\)
a)
\(\left(x+1\right)^2+x\left(2-x\right)\)
\(=x^2+2x+1+2x-x^2\)
\(=4x+1\)
b)
\(\left(x-2\right)^3-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=x^3-6x^2+12x-8-x^2+8\)
\(=-6x^2+12x\)
\(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)
\(=2x^3-3x-5x^3-x^2+x^2\)
\(=-3x^3-3x\)
\(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)
\(=2x^3-3x-5x^3-x^2+x^2\)
\(=\left(2x^3-5x^3\right)-3x+\left(-x^2+x^2\right)\)
\(=-3x^3-3x\)
_Chúc bạn học tốt_
a) -5xy(3x2y – 5xy +y2)
=-15x3y2+25x2y2-5xy3
b) (x + 8)2 -2(x + 8) (x – 2) + (x – 2)2
=[(x+8)-(x-2)]2
=(x+8-x+2)2
=102
=100
\(a,-5xy\left(3x^2y-5xy+y^2\right)=-15x^3y^2+25x^2y^2-5xy^3\)
\(b,\left(x+8\right)^2-2\left(x+8\right)\left(x-2\right)+\left(x-2\right)^2=\left[x+8-\left(x-2\right)\right]^2=\left[x+8-x+2\right]^2=10^2=100\)
A = (x - 2)(x + 2) - (x + 2)2
= x2 - 4 - x2 - 4x - 4
= -4x - 8 = -4(x + 2)